Case Study Approach in Community Empowerment Research in Indonesia - Faridl Widhagdha, Miftah; Ediyono, Suryo (Prospect Publishing, 2022)
Case study is one approach in qualitative research that was developed from the traditions of anthropology, sociology, and psychology. The case study approach focuses on the study of specific programs, events, activities, processes or units in a particular or contemporary context. This article is a literature review conducted on five dissertation articles that discuss the topic of community empowerment published by the Development Extension / Community Empowerment Doctoral Study Program, Graduate School, Sebelas Maret University in the period 2013-2020. As a result, the five dissertation articles reviewed used a case study approach as an analytical tool in dissecting community empowerment activities. A case studies must be supported by a deep understanding of the characteristics of the findings so that these approaches could have a large scientific impact.